2014
DOI: 10.1186/s40001-014-0057-5
|View full text |Cite
|
Sign up to set email alerts
|

Construction of microRNA and transcription factor regulatory network based on gene expression data in cardiomyopathy

Abstract: BackgroundCardiomyopathy is a progressive myocardial disorder. Here, we attempted to reveal the possible mechanism of cardiomyopathy at the transcription level with the roles of microRNAs (miRNAs) and transcription factors (TFs) taken into account.MethodWe firstly identified differentially expressed genes (DEGs) between cardiomyopathy patients and controls with data from the gene expression omnibus (GEO) database. DEGs were associated with the canonical pathways, molecular and cellular functions, physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…In addition, individual miRs were clustered with respect to predominant functional pathways constructed by ingenuity pathway analysis (Qiagen) (25,38). Although it must be recognized that posttranscriptional regulation by individual miRs encompasses multiple targets, predominant functional domains relevant to myocardial remodeling and function can be developed through ingenuity pathway analysis (7,14,44,53) and are shown in Table 1. For each functional domain, a composite fold change of all associated miRs relative to referent normal was calculated using the comparative C T method.…”
Section: Categorical Mir Abundance Distributionmentioning
confidence: 99%
“…In addition, individual miRs were clustered with respect to predominant functional pathways constructed by ingenuity pathway analysis (Qiagen) (25,38). Although it must be recognized that posttranscriptional regulation by individual miRs encompasses multiple targets, predominant functional domains relevant to myocardial remodeling and function can be developed through ingenuity pathway analysis (7,14,44,53) and are shown in Table 1. For each functional domain, a composite fold change of all associated miRs relative to referent normal was calculated using the comparative C T method.…”
Section: Categorical Mir Abundance Distributionmentioning
confidence: 99%
“…Increasing evidence show that miRNAs regulate generation of glucocorticoids in adrenal gland and in contrast, glucocorticoids also regulate cell survival, proliferation, and function partially through regulation of miRNA expression ( Clayton et al, 2018 ). For example, in humans, miRNA-30c-5p and miRNA-125b-5p regulated expression of genes involved in cardiomyogenesis or cardiac function via glucocorticoid-mediated signaling pathway ( Wang et al, 2014 ).…”
Section: Potential Mechanisms Of Glucocorticoids In Fetal Muscle Deve...mentioning
confidence: 99%
“…It was found that differentially expressed genes between cardiomyopathy patients and healthy donors were enriched for various pathways, of which GR signaling is the most significant. miRNA-30c-5p and miRNA-125b-5p play an essential role in the regulatory network of differentially expressed genes related to glucocorticoid signaling, which is implicated in cardiomyogenesis or cardiac function (Wang et al 2014).…”
Section: Mirnasmentioning
confidence: 99%